Assessing financial education methods: Principles vs. rules-of-thumb approaches. Issue 3 (2nd July 2016) - Skimmyhorn, William L.; Davies, Evan R.; Mun, David; Mitchell, Brian
ABSTRACT: Despite thousands of programs and tremendous public and private interest in improving financial decision-making, little is known about how best to teach financial education. Using an experimental approach, the authors estimated the effects of two different education methodologies (principles-based and rules-of-thumb) on the knowledge, self-assessed knowledge, financial self-efficacy, motivation to learn, willingness to seek advice, risk preferences, and time preferences of high-performing undergraduate students. They found both methods increased cognitive measures of knowledge and noncognitive measures of self-efficacy, motivation to learn, and willingness to take financial risks. They found few differences in the relative effectiveness of each method, although the principles methodology appears to generate larger gains in self-efficacy, while the rules-of-thumb method appears to reduce individuals' willingness to seek advice.